Discontinuities in the Telecom Industry: Strategic Choices for SingTel - Lee, Siak Kwee (2008)
This report examines the corporate strategy of SingTel and show how they can be derived from a combined analysis of its internal and external environment. An outside-in, position-based approach using the PorterÃÂÃÂ¢ÃÂÃÂÃÂÃÂs Five Forces (PFF) model is used to analyse the complexities and forces shrouding the industry with the aim of identifying the key opportunities and threats. An inside-out, resource-based approach using the Resource Based View (RBV) is also undertaken to reveal SingTelÃÂÃÂ¢ÃÂÃÂÃÂÃÂs key strengths and weaknesses. Interviews were also conducted with two key management executives within SingTel to gain a first hand understanding of the strategic issues from an insider perspective.